Infrared Thermography to Assess Thermoregulatory Reactions of Female Buffaloes in a Humid Tropical Environment - Brcko, Carolina Carvalho; Silva, Jamile Andréa Rodrigues da; Martorano, Lucieta Guerreiro; Vilela, Reíssa Alves; Nahúm, Benjamim de Souza; Silva, André Guimarães Maciele; Barbosa, Antônio Vinícius Corrêa; Bezerra, Andréia Santana; Lourenço Júnior, José de Brito (Frontiers in Veterinary Science, 2020)
This study employed infrared thermography to assess the thermoregulatory responses of female buffaloes reared in a hot and humid climate as a function of variations in time and the thermal environment, and to correlate rectal temperature with that of different body areas. The trial was carried out at Embrapa Eastern Amazon (01°26’S and 48°24’W) in Belém, PA, Brazil. 24 female buffaloes fed exclusively on pasture and exposed to the sun throughout the day in an open area were used. The animals were taken back to the corral at 6 A.M., 9 A.M., 12 P.M., 3 P.M., 6 P.M., and 9 P.M. for measurements of rectal temperature (RT), respiratory rate (RR), and body surface temperature (BST) using infrared thermography (IRT). Data on air temperature (AT), relative air humidity (RH), wind velocity (WV) and solar radiation (SR) were also recorded. A quadratic effect of AT, RH, SR, RR, and RT (P<0.01) was found as a function of measurement time. Between 12 P.M. and 3 P.M., AT, SR, RR, and RT values were the highest, while RH values were the lowest (P<0.05). WV was the highest between 12 P.M. and 9 P.M. A difference was found in RR and RT among the day’s times, with the highest values at 12 P.M. and 3 P.M. (P<0.05). The IRTs have a quadratic effect as a function of day’s times, with the highest levels between 12 P.M. and 6 P.M. and a reduction at 9 P.M. All IRTs are correlated with the physiological variables RR and RT, except for the IRT of the side of the back, which is not correlated with RT. The IRTs of the eye and cheek are correlated with RT (P<0.01) and with RR (P<0.05). Infrared thermography was efficient in evaluating the thermal stress of female buffaloes in hot and humid climates, and the technique can be used to evaluate the body temperature of these animals, since the rectal temperature was positively correlated with the temperature of the eye and cheek.